Implementation of a Centralized Telehealth-based Antimicrobial Stewardship Program (ASP) for 16 Small Community Hospitals (SCHs). (4th October 2017) - Veillette, John J; Vento, Todd; Gelman, Stephanie; Buckel, Whitney R; Jones, Peter S; Stanfield, Valoree; Adams, Mary; Repko, Katherine; Stenehjem, Edward
Abstract: Background: Innovative strategies are needed for ASP implementation in SCHs (<200 beds). Most SCHs lack ASPs that meet Joint Commission (JC) requirements and CDC core elements. Telehealth can help extend infectious diseases expertise and stewardship resources to such facilities. Methods: The Infectious Diseases Telehealth (IDt) program provides consultation and ASP support to 16 Intermountain SCHs (18-150 beds). Key stakeholders were identified at each site to establish formal ASPs. An IDt physician and pharmacist attended local meetings as ASP members to provide guidance. Centrally tracked antibiotic usage and resistance data were reviewed with each program to identify opportunities for improvement. Daily stewardship responsibilities were shared: front-line pharmacists were trained to review charts for appropriateness using automated electronic alerts, while the IDt pharmacist reviewed high priority alerts (e.g., positive blood cultures). Recommendations were made to local staff, or to the IDt physician in cases needing telehealth consultation. Results: ASPs were formed at 15/16 hospitals (1/16 had an existing ASP). Members included: local physician (15/16), local pharmacist (15/16), infection preventionist (16/16), quality representative (15/16), nursing (5/16), and administration (5/16). Collaborative data review led to 16 planned projects to improve antimicrobial prescribing. Eleven targeted specific drugs [carbapenems ( n = 6), piperacillin-tazobactam ( n = 1), fluoroquinolones ( n = 2), vancomycin ( n = 2)], and five aimed to improve processes [allergy assessment ( n = 2), order sets ( n = 2), and implementation of rapid diagnostics ( n = 1)]. Five of 16 ASPs documented full compliance with JC and CDC requirements, and 11/16 documented partial compliance (none were compliant prior to IDt implementation). Front-line pharmacists reviewed 3, 593 stewardship alerts during the first 7 months, leading to 826 interventions across 16 facilities. The IDt pharmacist reviewed 1, 198 alerts leading to 318 interventions. Conclusion: We established or augmented ASPs in 16 Intermountain SCHs through local empowerment, central data sharing, and IDt mentorship. Future goals include documenting improvement in antibiotic use and patient outcomes. Disclosures: All authors: No reported disclosures.